A literatura oral em contos populares do Ceará: a carnalidade em performance - Portella, Mirtes Maria de Oliveira (2008)
The purpose of this work is the investigation about conception of literary that is implied in the displacement of brazilian popular story from the verbal form to the writting form. As references, the edited storys contained in the book Brazilian Popular Stories - Ceará (2003) was taken as study object. This book was made from some colect of popular stories, which transcription methodology was worried about the allegiance to the verbal source, in order to preserve the vocal marks of the storytellers. The analysis corpus had as election criterion the capacity of survival and conservation of the stories João and Maria , Maria Borralheira and Dom Anin , inspired in the conceptions of voice, body and performance elucidated by the medievalista Paul Zumthor (1915 - 1984). During the development of this research strategies of text reformulation could be revealed in the tranfiguration of verbal form to the writing one, which gives to the writting form a hibrid caracter, between the letter and voice. To inquire about how and when the orality marks inscribed in the texts became condition to consider them poetical, diverse linguistic characteristics was analysed, such as: phonological, morphologic and syntactic, besides conversational and prosaisms markers of orality, which had vivified the narrative speech intensifing the presence of narrators performance: initiatives that not just allow the decoding of graphical signs but also make possible the recognition of a listening, that is a determinative principle of the poetical essence of literature. The analysis of the narratives demonstrated that even being coherent with the orality elements present in the speaks of the storytellers, the transcription also bring some inherents caracteristics of the publishing process. Those process transit between the tradition and memory, but are paradoxicalally unfinished because are always related to its context of production. The stories are constituent of a dialogal and discursive net, and in this condition are presented by social and historical entities at the performance moment. When represented in the written text, the speeches made by those entities suggest narrators in parallel with the original storytellers. So, in this context the reader is in charge to rescue trough the letter the vocality and performance, attributing some carnal e material characteristics to the transmission process